THE REALITY OF EXTERNAL AUDIT IN IRAQ AND ITS IMPACT ON THE VARIOUS CRISES IN THE ENVIRONMENT OF INDUSTRIAL COMPANIES - Lec. Fatimah Flayyih oudah; Lec. Ali Mahdi Hameed; Lec. Ali Miri Hassan (Scholars Digest Publishing, 2023)
Purpose: The study aims to demonstrate the reality of external audit in light of crises and related, the work performed by the external auditor in the Iraqi environment in the environment of the industrial sector, F What are the various audit crises and how can they be managed, the study shows the impact and correlation between the reality of external audit in Iraq and the various crises in the environment of industrial companies. In order to achieve the objectives of the study and solve its problem, the authors proposed the following two hypotheses:( There is a significant moral impact between the reality of external audit and the various crises in the Iraqi environment Industrial At an indicative level 0.05.) Theoretical framework: There is a significant correlation between the reality of external audit and the various crises in the Iraqi environment Industrial At an indicative level 0.05. The necessary information was collected to complete the study in its theoretical and applied aspects through the available literature, but in its practical framework. Design/methodology/approach: In order to achieve this, the industrial sector of companies was relied upon (Baghdad soft drinks company-Al Hilal industrial company-ready-made clothing production company-Modern Chemical Industries Joint Stock Company- Al Mansour Pharmaceutical Industries Company) Its shares are listed on the Iraqi Stock Exchange and for a period of (2016 – 2020), Market releases of the same sample. The authors relied on Both deductive and analytical approaches, Faithful represented the limits of spatial study in the banking sector, while the time limits are represented by the years of 2016-2020. Findings : F The study found that there is a correlation between the reality of external audit and the management of various crises, it amounted to(0.267-) It is a negative relation i.e. (Weak inverse relationship) That is, the higher the quality of the external auditor's performance, the lower the crises experienced by industrial companies, which are at a lower moral level than (0.05),This indicates that there is a significant correlation between the reality of external audit and the various crises in the Iraqi industrial environment at a significant level 0.05. It turned out that the fact of external audit contributed to the explanation of the amount of (0.872) One of the differences in various crises, While the residual value represents factors that are not included in the study area. Based on the above, the results show the validity of the hypothesis claim " The presence of a significant impact between the reality of external audit and the various crises in the Iraqi industrial environment at the level of significant 0.05. Research, Practical & Social implications: It is necessary to improve the reality of external auditing in Iraq, due to its contribution to crisis management. Originality/value: Organizations interested in external auditing should organize and manage the reality of external auditing, given the urgent need for crisis management.
Keywords: The reality of external audit-various crises-various crisis management.